Place of residence does matter for educational integration : the relevance of spatial contexts for refugees’ transition to VET in Germany - Meyer, Franziska [Verfasser]; Winkler, Oliver [Verfasser] (My University, 2023)
„For the mostly young refugees who arrived in Germany around 2015/2016, completing vocational education and training (VET) represents the most promising opportunity for professional and social integration. However, access opportunities to VET are characterized by spatial inequalities: German districts vary considerably according to labour market structure, economic productivity and demographic development, which constitute the supply and demand for training places in the dual VET sector, to which refugees predominantly have access. This paper examines if the transition chances of young refugees aged 18–30 to VET depend on their place of residence. For this, we analysed the IAB-BAMF-SOEP Survey of Refugees (n = 5216) using multi-level discrete-time event history analysis. On the supply side, higher economic productivity (measured by GDP), a low unemployment rate and a greater number of small versus large businesses in the district are positively associated with refugees’ transition chances. On the demand side, an increasing number of school leavers with no school-leaving certificate and of refugees in the district are negatively associated with the respective chances. Our results suggest that spatial characteristics essentially matter for young refugees’ training opportunities and thus support recommendations to reform current distribution policies, in which central spatial contextual factors remain largely disregarded.“ (authors‘ abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; G 2.1.4 Regionalisierung; 370; Flüchtling; Berufseinmündung; Ausbildungschance; Regionale Faktoren; Regionale Disparität; Einflussfaktor